Legal Regulation of States and International Journalistic Organizations Interaction in the Eurasian Media Space - G. V. Alexeyev; O. N. Kharina (Евразийская интеграция: экономика, право, политика, 2025)
Progress towards deliberative democracy in the post-Soviet reality requires legal conditions for countering violent extremism through sustainable development of journalistic unions.   Aim and tasks. The development of the Eurasian media space through the involvement of post-Soviet countries in equal political dialogue presupposes the protection of the interests of state media and independent journalistic unions. Digital democracy needs effective legal institutions for free and competent journalism. Providing conditions for legal interaction between States and journalistic unions in the Eurasian information space should be based on the improvement of international legal guarantees for the quality of journalistic work and commitment to democratic values.   Methods. Case study of legal interaction between States and journalists is intended to expand the possibilities of self-regulation in the media sphere and promote narrative analysis to solve the problems of extremism and information wars in the post-Soviet space.   Results. The development of statehood in the post-Soviet space should be accompanied by responsible behavior of international journalistic organizations and recognition of their competence in organizing intellectual competition for the audience’s attention. Abuse of journalists’ rights, monopolization of the regional media market, low quality of tactical media and insufficient competence of media discourse participants pose critical threats to the information security of states, reducing the quality of journalism throughout the post-Soviet space.   Conclusions. Professional and creative unions of journalists are responsible for the reproduction of qualified professionals, the protection of intellectual and labor rights of their members, compliance with professional ethics and the promotion of traditional values in the media space. The solution of the tasks facing national journalistic organizations presupposes the organization of international cooperation in national interests.   The task of international journalistic unions is to smooth out conflicts by organizing a professional polylogue.   Disqualification of national journalistic unions from international journalistic organizations leads to the violation of the rights of state media journalists and provokes the escalation of conflict in the information space. The protection of the rights of creative authors and journalists working on assignment from the editorial boards of state and private media requires legal certainty in defining the framework of acceptable narratives, as well as maintaining an independent platform for professional interaction between all active participants in the political discourse who are interested in normalizing the military and political situation by creating an atmosphere of strategic trust in the post-Soviet space.